Synthesis and evaluation of novel bioactive composite starch/bioactive glass microparticles - Silva, G. A. (2004)
The aim of the development of composite materials is to combine the most desired properties of two or more materials. In this work, the biodegradable character, good controlled-release properties, and natural origin of starch-based biomaterials are combined with the bioactive and bone-bonding properties of bioactive glass (BG). Novel, bioactive composite starch-BG microparticles were synthesized starting from a blend of starch and polylactic acid (50%/50% wt) with BG 45S5 powder using a simple emulsion method. Morphological and chemical characterization showed that these particles exhibited a spherical morphology with sizes up to 350 m and that BG 45S5 was incorporated successfully into the composite particles. Upon immersion in a solution simulating body fluids, for periods up to 3 weeks, their bioactive nature was confirmed, as a calcium-phosphate layer resembling biological apatite was formed onto their surface. The short-term cytotoxicity of these materials was also tested by placing 24-h leachables of the materials extracted in culture medium in contact with a fibroblastic cell line (L929) up to 72 h. At this time period, two biochemical tests - MTT and total protein quantification - were performed. The results showed that these materials are not cytotoxic. These results constitute the basis of future encapsulation studies using bone-acting therapeutic agents such as bone morphogenetic proteins or other bone-relevant factors. The particles developed here may be very useful for applications in which controlled release, degradability, and bone-bonding ability are the main requirements.